2006
DOI: 10.1177/0885412206292259
|View full text |Cite
|
Sign up to set email alerts
|

Social Diversity and Economic Development in the Metropolis

Abstract: Theories of regional economic development are increasingly focused on understanding the reasons for metropolitan economic growth. The "creative capital" perspective argues that such growth is extremely dependent on the presence of four main conditions: technology, talent, tolerance, and good quality of place. This article examines evidence for the importance of tolerance in promoting metropolitan economic development. Through his analysis, Richard Florida studied the association of economic growth with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 58 publications
(77 reference statements)
1
36
0
Order By: Relevance
“…Comparing creative and noncreative households in Bangkok, Thailand, Mansury, Tontisirin, and Anantsuksomsri (2012) concluded that creative households were more likely to reside near rail stations, 'top schools', shopping malls, and public parks within the city's 'inner-ring.' Crucially, to the authors' knowledge no study has yet empirically examined diversity as a potential factor in the intra-urban residential location of creative class workers, despite the claim that openness and tolerance are key aspects of the creative class ethos (Florida, 2002;Thomas & Darnton, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Comparing creative and noncreative households in Bangkok, Thailand, Mansury, Tontisirin, and Anantsuksomsri (2012) concluded that creative households were more likely to reside near rail stations, 'top schools', shopping malls, and public parks within the city's 'inner-ring.' Crucially, to the authors' knowledge no study has yet empirically examined diversity as a potential factor in the intra-urban residential location of creative class workers, despite the claim that openness and tolerance are key aspects of the creative class ethos (Florida, 2002;Thomas & Darnton, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…For an attempt to operationalise all Jacobs's conditions, see for instance Sung et al (2015). 11 For the critical debate on this point and discussion on empirical evidence, see for instance Desrochers (2001a), Storper and Manville (2006), Thomas and Darnton (2006), Leppälä (2011a, 2011b), Syrett and Sepulveda (2011), Kemeny (2012), Nathan (2015 and Rodriguez-Pose and Hardy (2015).…”
mentioning
confidence: 99%
“…Studies show that residents of gentrified properties are, more often than not, already city dwellers, merely relocating to better accommodations [56,59,[62][63]. In more than half the cases, the gentry are middle-class Blacks, immigrants from Asia and Latin America, gays, liberal academics, artists/bohemians, or others who are critical of the status quo [4,61,[64][65][66]. None of these groups are viewed by Conservative Elite as part of their coalition or constituency.…”
Section: The Spatial Semiosis Of Real Estate Deve-lopment and The Conmentioning
confidence: 99%
“…In other cases, rentiers may be merely acting as the Conservative's protector of a symbolically important or prestigious space in the city, or reclaiming it from the 'other.' Examples of this include historic or waterfront district redevelopments that are meant to appeal to tourists, rather than city residents [4,65,67].…”
Section: The Spatial Semiosis Of Real Estate Deve-lopment and The Conmentioning
confidence: 99%